PENGARUH MODEL LEARNING CYCLE 5E BERBANTUAN THINGLINK TERHADAP PARTISIPASI BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI - Fi'izzatirodian; Masyhuri; Mila Noviana (Jurusan P. IPS, FKIP, Universitas Mataram, 2026)
The low level of student learning participation in sociology learning is indicated by the lack of student involvement in asking questions, expressing opinions, discussing, and concluding the learning material. This study aims to determine the effect of the 5E learning cycle model assisted by thinglink media on student learning participation in Sociology subjects. This study uses a quantitative approach with a quasi-experimental type and a posttest only design with a non-equivalent control group design. The study population was all 200 students of grade XI of SMA Negeri 1 Gunungsari. The research sample was determined using a simple random sampling technique after class matching so that class XI-I was obtained as the experimental class and class XI-K as the control class, each consisting of 33 students. The research instrument was a student learning participation observation sheet that had met the validity and reliability tests. Data analysis was carried out through normality tests, homogeneity tests, and hypothesis tests using independent samples t-tests. The results showed that the average student learning participation in the experimental class was 82.42, higher than the control class at 71.51. The results of the hypothesis test obtained a Sig. value. (2-tailed) of 0.000 < 0.05 and the calculated T value (5.203) > Ttable (1.998) so that H0 is rejected and Ha is accepted. Thus, it can be concluded that the 5E learning cycle model assisted by thinglink media has a significant effect on student learning participation in Sociology subjects at SMA Negeri 1 Gunungsari. Keywords: 5E Learning Cycle; Thinglink; learning participation